Prognostic Factors of Renal Involvement in Systemic Sclerosis - Edoardo Rosato (Kidney & Blood Pressure Research, 2018)
Background/Aims: Renal involvement is common in systemic sclerosis (SSc), including asymptomatic reduction of glomerular filtration rate (GFR), increased renal resistance indices, scleroderma renal crisis (SRC) and ANCA-associated vasculitis. The aim was to evaluate type and evolution of renal involvement for a period of five years. Methods: 121 SSc patients (100 F, 21 M) with mean age of 54.9 ± 13.8, disease duration of 9 ± 6 years, of which 62 had a diffused form and 59 limited form were enrolled. All patients were screened annually for renal function by laboratory examination, ultrasound and color Doppler ultrasound of renal arteries. Results: Over the five-year observation period, 6 SRC (3 M, 3 F) occurred, four of which required dialysis. One patient developed ANCA-related proliferative glomerulonephritis and the other one acute tubular necrosis. The remaining 113 patients had a preserved renal function (serum creatinine 0.75 ± 0.24 mg/dl, GFR 93.8 ± 20 ml/min, 24h proteinuria 0.20 ± 0.15 g). Doppler indices of intrarenal arterial stiffness increased with progression of capillaroscopic damage and with presence of digital ulcers. A negative correlation was observed between estimated GFR and pulsatile index (p< 0,05, r=-0.198), resistive index(p< 0,01, r=0.267), S/D ratio (p< 0,01, r=-0.237). Conclusion: In SSc patients, renal function was normal for 4.1 years despite the presence of increased intrarenal arterial stiffness. SRC was observed in 4.9% of SSc patients. In SSc patients, a periodic follow-up based on clinical and laboratory evaluation, colorDoppler ultrasound and, in some cases, renal biopsy is required to evaluate renal involvement.